2020
DOI: 10.1136/bmjopen-2020-038438
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical therapy in addition to occlusal splint in myogenic temporomandibular disorders: protocol of a randomised controlled trial

Abstract: IntroductionTemporomandibular disorders (TMDs) are considered a collection of musculoskeletal conditions involving the masticatory muscles, the temporomandibular joint and associated structures. The myogenous group appears to represent the most frequently diagnosed category. In the context of a multimodal approach, splint therapy and musculoskeletal physiotherapy are often considered as a preferred therapy. The purpose of this study will be to investigate the effects of musculoskeletal physiotherapy combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Physiotherapy, also termed physical therapy or exercise therapy, has been proposed to play a vital role, especially in the management of myofascial pain complaints for patients with TMD [ 8 , 48 , 68 , 69 , 70 , 71 , 72 ]. It can be subdivided into self-exercise conducted by patients at home or manual therapy by a trained practitioner [ 73 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Physiotherapy, also termed physical therapy or exercise therapy, has been proposed to play a vital role, especially in the management of myofascial pain complaints for patients with TMD [ 8 , 48 , 68 , 69 , 70 , 71 , 72 ]. It can be subdivided into self-exercise conducted by patients at home or manual therapy by a trained practitioner [ 73 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…During the analysis of full-text versions, some studies were rejected due to different TMD diagnoses than muscle pain in the study group, inclusion of TMD patients without pain, no proper index to measure the pain level, or no control group [ 34 38 ]. One study was not completed during the writing of this systematic review [ 39 ]. Details on the selection of studies are shown in a flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The educational program was provided throughout a brochure to all participants by the same clinician (CI). It consisted of a series of advices aimed at increasing awareness about oral behaviours and their detrimental effect on the masticatory muscles 20 …”
Section: Methodsmentioning
confidence: 99%